Extranodal Marginal Zone Lymphoma of the Thyroid with Extensive Amyloid Deposition: A Rare Case Presentation. (9th November 2022) - El-Dana, F; Eltahir, M; Siatecka, H; Cox, B; Perez, M
Abstract: Introduction/Objective: Extranodal marginal zone lymphoma (MZL) is a rare indolent tumor with the potential of recurrence and systemic spread. Thyroid involvement is infrequently reported, and generally seen in the context of Hashimoto thyroiditis. Additionally, amyloid deposition is an exceptional complication of extranodal MZL. We report an unusual case of a 65-year-old woman with a rapidly growing symptomatic nodule of the right thyroid lobe and a previous inconclusive FNA showing benign lymphoid tissue. She was taken to the OR for diagnostic right thyroid lobectomy with neck level 6 dissection. Methods/Case Report: The specimen was sent for histologic evaluation, and showed thyroid with marked amyloid deposition, highlighted by Congo Red special stain, distorting normal architecture. Additionally, significant small atypical lymphoid infiltrate was present. Neoplastic lymphocytes were positive for CD20, PAX5 and CD43. Kappa light chain restriction by kappa ISH stain indicated monoclonality. Conversely, CD138, CD10, BCL6 and CyclinD were negative. Ki-67 demonstrated a 15-20% proliferation index. The germinal centers of the secondary follicles demonstrated diminished CD10 and BCL-6 consistent with follicular colonization by neoplastic lymphocytes. One of the regional lymph nodes displayed involvement by lymphoma with amyloid deposition. Medullary carcinoma of the thyroid was ruled out on the basis of incompatible histologic and immunohistochemical profile. Results (if a Case Study enter NA): NA Conclusion: While Medullary carcinoma and amyloid goiter are among the top differentials for extensive amyloid deposition in the thyroid gland, we illustrate the need for judicious review of clinical history and careful consideration of immunohistochemistry workup to establish the unusual diagnosis of extranodal MZL of the thyroid with extensive amyloid deposition.